Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Student Team Achievement Division di Kelas IV Sekolah Dasar - Astuti, Ria Afri; Eliyasni, Rifda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This study aims to describe the use of thematic learning outcomes the student teams achievement model in the grade IV of SDN 56 Anak Air. This research is a classroom action research (CAR) that uses a qualitative and quantitative approach. Conducted in two cycles, with three meetings covering four stages, namely planning, implementation, observation, and reflection. The subjects of this study were researchers, teachers, and fifth grade students of SDN 56  Anak Air, totaling 30 people. The results of the study were: (1) the percentage of lesson plan observation was 79.16%, an increase of 94,44%. (2) Teacher activities 75%, an increase of 96,42%. (3) Student activities 75%, an increase of 96,42%. It can be concluded that the Student Teams Achievement model can possibly improve student learning outcomes.